2022
DOI: 10.2217/pme-2021-0091
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of an exome sequencing training course for medical interpreters

Abstract: Aim: As genomic medicine reaches more diverse populations, there is an increased need for healthcare interpreters who understand and can effectively interpret genomics concepts. Methods: We designed a course for healthcare interpreters on exome sequencing to enhance their preparedness for genomic results disclosure appointments in the Cancer Health Assessments Reaching Many (CHARM) study and beyond. The course was evaluated via pre/post surveys and qualitative interviews. Results: 23 interpreters completed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Our interview findings indicated that interpreters' felt their proficiency was limited by the infrequency of genetics appointments to develop skills and remember vocabulary. This aligns with the result of our interpreter training study, in which we found that the training significantly increased interpreters' confidence, but not knowledge (Riddle et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our interview findings indicated that interpreters' felt their proficiency was limited by the infrequency of genetics appointments to develop skills and remember vocabulary. This aligns with the result of our interpreter training study, in which we found that the training significantly increased interpreters' confidence, but not knowledge (Riddle et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…To address the need for medical interpreters' proficiency in fundamental genetics and genomics concepts and vocabulary, specialized training could improve overall performance and reduce errors. Our team has created an in‐depth course (8 h over 2 days) that builds on findings described here as well as on the results of our interpreter training study (Riddle et al, 2022). It is available via the HealthCare Interpreters Network (HCIN), where other continuing education classes and workshops funded by the American College of Medical Genetics are also available, to enhance interpreters' understanding of genetic/genomic medicine (Health Care Interpreter Network, n.d.).…”
Section: Discussionmentioning
confidence: 98%
“…Medical translators from the same ethnic background and culture can help clinicians to provide a family‐centered model that considers different preferences and decision‐making. Some centers provide specific training to translators in genomic medicine 199 . The development of patient‐facing material and additional informative resources through medical translation is another mechanism to support families.…”
Section: Discussionmentioning
confidence: 99%
“…Some centers provide specific training to translators in genomic medicine. 199 The development of patient-facing material and additional informative resources through medical translation is another mechanism to support families. These resources can be used complementarily with genetic counselling (where available) to better support the diverse multicultural community.…”
Section: General Genetic Counselling Considerationsmentioning
confidence: 99%
“…For example, training for medical interpreters who interpret in genetic counseling sessions may be a good option for GCs working with the same group of medical interpreters regularly in an effort to increase interpreters' preparedness (e.g., session content and format, common terminology) for sessions. Riddle et al (2022) found that a course aimed at enhancing interpreters' preparedness for genomic results disclosure appointments was effective at improving interpreters' confidence during sessions. Alternatively, English‐speaking GCs could consider trainings aimed at improving communication for limited health literacy patients, i.e., incorporating methods like the teach‐back method and using simplified language in sessions, as there are several published studies on different models and interventions (Joseph et al, 2019; Riddle et al, 2021; van der Giessen et al, 2020; van der Giessen, Ausems, et al, 2021; van der Giessen, Fransen, et al, 2021; van der Giessen, van Dulmen, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%